Subclinical Cardiovascular Damage and Fat Utilization in Overweight/Obese Individuals Receiving the Same Dietary and Pharmacological Interventions - Montalcini, Tiziana (Nutrients, 2014)
Subclinical organ damage precedes the occurrence of cardiovascular events in individuals with obesity and hypertension. The aim of this study was to assess the relationship between fuel utilization and subclinical cardiovascular damage in overweight/obese individuals free of established cardiovascular disease receiving the same diet and pharmacological intervention. In this retrospective study a total of 35 subjects following a balanced diet were enrolled. They underwent a complete nutritional and cardiovascular assessment. Echocardiography and ultrasonography of the carotid arteries was performed. The respiratory quotient (fuel utilization index) was assessed by indirect calorimetry. A total of 18 had left ventricular concentric remodeling, 17 were normal. Between these two groups, a significant difference of intima-media thickness was showed (p = 0.015). Also a difference of respiratory quotient was shown with the highest value in those with remodeling (p = 0.038). At univariate and multivariate analysis, cardiac remodeling was associated with respiratory quotient (RQ) (p = 0.04; beta = 0.38; SE = 0.021; B = 0.044). The area under the receiver operating characteristic (ROC) curve for respiratory quotient to predict remodeling was 0.72 (SE = 0.093; p = 0.031; RQ = 0.87; 72% sensitivity, 84% specificity). The respiratory quotient is significantly different between those participants with and without cardiac remodeling. Its measurement may help for interpreting the (patho)physiological mechanisms in the nutrients utilization of obese people with different response to dietary or pharmacological interventions.